2018
DOI: 10.1002/anie.201806036
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Selective C−S Bond Formation at C−Br over C−OTf and C−Cl Enabled by an Air‐Stable, Easily Recoverable, and Recyclable Palladium(I) Catalyst

Abstract: This report widens the repertoire of emerging Pd catalysis to carbon-heteroatom, that is, C-S bond formation. While Pd -catalyzed protocols may suffer from the formation of poisonous sulfide-bound off-cycle intermediates and lack of selectivity, the mechanistically diverse Pd catalysis concept circumvents these challenges and allows for C-S bond formation (S-aryl and S-alkyl) of a wide range of aryl halides. Site-selective thiolations of C-Br sites in the presence of C-Cl and C-OTf were achieved in a general a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
63
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 81 publications
0
63
0
Order By: Relevance
“…Meanwhile, diverse substituents can be introduced at the 4‐position of the isochromenones , . Although C sp 2 –S bond formation had been widely reported, the preparation of 4‐sulfenylisochromenones has been less explored due to the limitation on their synthetic strategies. Larock and co‐workers reported that by treating alkynes with the electrophilic sulfenyl chloride, sulfoesterification occurred to give the corresponding 4‐(sulfenyl)isochromenones (Scheme a).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, diverse substituents can be introduced at the 4‐position of the isochromenones , . Although C sp 2 –S bond formation had been widely reported, the preparation of 4‐sulfenylisochromenones has been less explored due to the limitation on their synthetic strategies. Larock and co‐workers reported that by treating alkynes with the electrophilic sulfenyl chloride, sulfoesterification occurred to give the corresponding 4‐(sulfenyl)isochromenones (Scheme a).…”
Section: Introductionmentioning
confidence: 99%
“…Since Migita first developed the cross-coupling of thiols with aryl halides for the carbon-sulfur bond construction, [4] many transition metals have been explored for this transformation, including palladium, [5] nickel, [6] copper, [7] cobalt [8] and so on. [9] Nearly all catalytic approaches select aryl thiols as the source of sulfur.…”
Section: Palladium-catalyzed Cross-coupling Of Aryl Thioacetates and mentioning
confidence: 99%
“…A wide range of thioacetates and chloro(hetero) arenes can be employed for the preparation of aryl sulfides in good to excellent yield.Transition metal catalyzed carbon-carbon and carbon-heteroatom bond formations have attracted significant interest because of their wide application in synthetic organic chemistry, and emerged as a tremendously powerful synthetic tools for the carbon-carbon and carbon-heteroatom bond constructions. [1] Among carbon-heteroatom bond formations, carbon-sulfur bond formation has been extensively studied due to its important role in pharmaceutical field [2] and material science [3] over past decade.Since Migita first developed the cross-coupling of thiols with aryl halides for the carbon-sulfur bond construction, [4] many transition metals have been explored for this transformation, including palladium, [5] nickel, [6]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our objective was to develop an operationally simple and direct methodt hat minimizes toxic by-products and unwanted side reactions under mild conditions (Scheme 1).We recently showedt hat dinuclear Pd I catalysis is ap romising concept to circumvent poisonous ate complexes in catalysis. [13] In this context,t he iodide-bridged dimer 1 has been shownt ot rigger dinuclearc atalysis cycles whiled isplaying superior stability properties:D imer 1 is completely stable towards oxygen as as olid and can be stored on the bench. [13,14] Our previous work has indicated that Pd I catalysis will be suc-Scheme1.Key challenges in metal-catalyzed C(sp 2 )ÀSe bond formation.…”
mentioning
confidence: 99%